Biophysical Characterization of Membrane Phase Transition Profiles for the Discrimination of Outer Membrane Vesicles (OMVs) From Escherichia coli Grown at Different Temperatures - Sarra, Angelo; Celluzzi, Antonella; Bruno, Stefania Paola; Ricci, Caterina; Sennato, Simona; Ortore, Maria Grazia; Casciardi, Stefano; Del Chierico, Federica; Postorino, Paolo; Bordi, Federico; Masotti, Andrea (Frontiers in Microbiology, 2020)
Dynamic Light Scattering (DLS), Small Angle X-ray Scattering (SAXS) and Transmission Electron Microscopy (TEM) are physical techniques widely employed to characterize the morphology and the structure of vesicles such as liposomes or human extracellular vesicles (exosomes). Bacterial extracellular vesicles are similar in size to human exosomes, although their function and membrane properties have not been elucidated in such detail as in the case of exosomes. Here, we applied the above cited techniques, in synergy with the thermodynamic characterization of the vesicles lipid membrane using a turbidimetric technique to the study of vesicles produced by Gram-negative bacteria (Outer Membrane Vesicles, OMVs) grown at different temperatures. This study demonstrated that our combined approach was useful to discriminate vesicles of different origin or coming from bacteria cultured under different experimental conditions. We envisage that in a near future the techniques employed in our work will be implemented further to discriminate complex mixtures of bacterial vesicles, thus showing great promises for biomedical or diagnostic applications.